2015
DOI: 10.1039/c5lc00379b
|View full text |Cite
|
Sign up to set email alerts
|

Partitioned EDGE devices for high throughput production of monodisperse emulsion droplets with two distinct sizes

Abstract: We present a novel microfluidic EDGE (Edge based Droplet GEneration) device with regularly spaced micron-sized partitions, which is aimed at upscaling of o/w emulsion preparation. By this means, remarkably higher pressure stability was obtained, and two orders of magnitude higher droplet formation frequency was achieved compared to regular EDGE devices. Interestingly, we observed two different monodisperse droplet formation regimes for plateaus that were 2 micrometres in height, and to the best of our knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 35 publications
1
60
0
Order By: Relevance
“…For example, we have made adjustments to the EDGE (Edge-based Droplet GEneration) device, which is unique in its ability to produce multiple droplets from one droplet formation unit. In doing so, we have increased its throughput 100-fold and also found that we could operate the device in two stable droplet formation regimes [106]. We even have taken the first steps toward upscaling [107,112], in which we are at the border of manufacturing possibilities.…”
Section: Emulsification Processesmentioning
confidence: 98%
“…For example, we have made adjustments to the EDGE (Edge-based Droplet GEneration) device, which is unique in its ability to produce multiple droplets from one droplet formation unit. In doing so, we have increased its throughput 100-fold and also found that we could operate the device in two stable droplet formation regimes [106]. We even have taken the first steps toward upscaling [107,112], in which we are at the border of manufacturing possibilities.…”
Section: Emulsification Processesmentioning
confidence: 98%
“…Numerous passive high-throughput droplet production techniques have been described, each featuring a unique set of advantages and drawbacks, 7 for example MCE, 29,38 EDGE 31,32 or 'millipede'. 28,39 Parallel passive emulsifying chips can be operated both horizontally (if the continuous phase is continuously supplied to transport the droplets away from the DFU 29,31 ) and vertically (aligning the DFU with the gravitational field allows buoyancy to evacuate the droplets away from the step, as shown here and by Stolovicki et al 40 ).…”
Section: Comparison With Current State-of-the-art Devicesmentioning
confidence: 99%
“…in the 'millipede' device 28 or in an up-scaled microchannel emulsifier. 29 Two well-known passive emulsification methods are microchannel emulsification (MCE) 30 and edge-based droplet generation (EDGE), 31,32 both shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Both effects counterbalanced, and ultimately the productivity of metal EDGEs was approximately the same as found for the regular EDGE devices. When re-structuring the plateaus into many small plateaus as done in the work of Sahin and Schroën [ 51 ], it is possible to increase the productivity considerably; both the number of droplet formation points and the pressure stability are in that case increased.…”
Section: Edge Devicesmentioning
confidence: 99%